The Role of Perceived Ease of Use in the Adoption of Quizlet for Vocabulary Acquisition in Chinese EFL Contexts - Huanting, Pan; Rokiah, Paee; Roslan, Ali (IJISRT Paper Publishing, 2024)
This study investigates the perceived ease of use of Quizlet among Chinese college English as a Foreign Language (EFL) learners, focusing on vocabulary acquisition. Utilizing a mixed-methods approach, the research combined quantitative data from a survey (n = 95) and qualitative insights from semi-structured interviews (n = 24) following an 8-week Quizlet intervention. The quantitative results revealed high satisfaction with Quizlet, evidenced by a mean score of 3.96 on a 5-point Likert scale, highlighting its intuitive interface and multimedia features. Qualitative findings supported these results, identifying key themes such as user-friendly navigation, ease of becoming proficient and effective vocabulary learning through interactive modules. The study emphasizes the critical role of user-centered design in educational technology, suggesting that well-designed tools like Quizlet can significantly improve vocabulary acquisition and learner engagement. These insights advance the understanding of digital tool adoption in EFL contexts and offer practical recommendations for educators and developers.